Influence of micron WC addition on the microstructure and mechanical properties of ultrafine WC–Co cemented carbides at the elevated temperature - Liu, C.; Lin, N.; He, Y.H.; Liu, W.S.; Ma, Y.Z. (Сверхтвердые материалы, 2018)
In this paper, the influence of micron-grained WC additions with the different grain sizes on the microstructure and hardness of ultrafine WC–Co cemented carbides at the elevated temperature were investigated by the scanning electron microscope and mechanical properties test. The Vickers hardness and transverse rupture strength of hardmetals were measured at temperatures ranging from room temperature to 800 °C. The results show that the addition of micron-sized WC particles can lead to the increase of fracture toughness and slow the decreasing of hardness at the elevated temperature.